Treatment Options for Intracranial Epidural Hematoma - An Integrative Review of the Past Three Decades - Carlos Umberto Pereira; Lauro Roberto de Azevedo Setton (Brazilian Neurosurgery)
Introduction Acute epidural intracranial hematoma (IEH) has been considered one of the most relevant neurosurgical emergencies in recent decades due to its high potential for morbidity and mortality. Early diagnosis followed by appropriate treatment results in a more favorable prognosis considering its rapid progression.